EFISIENSI BIAYA DENGAN PENERAPAN SISTEM ACTIVITY BASED MANEGEMENT (ABM) UNTUK MENENTUKAN HARGA POKOK PRODUKSI - Nurul Prayugho; Suwignyo Widagdo; Lia Rachmawati (Universitas Muhammadiyah Jember, 2021)
Abstract: This study aims to determine the efficiency of production costs of PT.Perkebunan Nusantara XII Kebun Mumbul RSS (Ribbed Smoked Sheet) Factory after the implementation of Activity Based Management (ABM).This type of research is descriptive qualitative. This research was conducted by identifying the activities that occur during the production process. Where the company data that has been collected will be compiled, processed, and analyzed to determine value-added and non-value added activities and impose costs into activities according to the amount of resources used or use direct loading to activities. Then compared with the theories that have existed so far. From the results of the comparison, a conclusion was drawn. The results of this study indicate that the application of the Activity Based Management(ABM)method at the RSS (Ribbed Smoked Sheet) factory can lead to production cost efficiency. This is because the amount of production costs in the ABM method results in lower production costs compared to the calculation of conventional methods.Keywords:efficiency, ABC, ABM